Stakeholders’ perspective on the economic cost of managing the invasive Navua sedge in tropical Queensland, Australia - Olusegun O Osunkoya; Boyang Shi; Kunjithapatham Dhileepan (Weed Technology)
Weeds incur up to A$4 billion in economic loss annually to Australian agriculture. Despite this knowledge, few quantitative data exist on yield loss and control costs caused by weeds. This article discusses the economic cost of managing the invasive Navua sedge weed to the grazing and cropping (sugarcane) industries of northern Queensland, Australia, following its introduction into the region in the 1970s. Between 2020 and 2022, through a survey questionnaire distributed to affected farmers, information on control cost, yield loss, and infestation history were documented. Collated data were analyzed using primarily nonparametric statistics due to the skewed or qualitative nature of many of the responses. The weed has invaded farming properties over the past 10 to 20 yr, the infestation level is considered to be low to moderate (median, 22.5%), and it varies appreciably among properties. The median cost of managing Navua sedge was A$72.91/ha when the study was conducted (the current value is now A$82.06). Neither this cost nor the type of management tactics (chemical vs. integrated weed management [IWM]) did not vary between land use types; however, labor, relative to chemical and machinery costs, was the greatest expense. The currently approved herbicide, halosulfuron-methyl (Sempra), is largely ineffective in controlling the weed due to its inability to deplete the weed’s belowground tubers. Correlation analyses suggest that control costs will continue to increase with increasing Navua sedge infestation over time, especially in grazing lands. Farmers are highly aware of the challenge of managing this new weed. Farmers are using a myriad of strategies, including being willing to impose strict biosecurity measures and IWM tactics, while waiting for more effective herbicides and promising biocontrol agents to minimize the spread and impact of the weed.